2017
DOI: 10.3329/bhj.v31i2.32379
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Bangladesh: A Review

Abstract: Abstract:Like elsewhere, cardiovascular disease (CVD) is an increasingly important cause of morbidity and mortality in Bangladesh. Over the past few decades, because of epidemiological transition, the prevailing disease pattern in this country changed from predominantly communicable to predominantly non-communicable disease, CVD contributes to the latter a lot. Actually, CVD particularly coronary artery disease (CAD) is getting epidemic proportion day by day. Hypertension and heart failure are on the rise, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 69 publications
(89 reference statements)
1
36
1
Order By: Relevance
“…Epidemiological studies have revealed that the prevalence of CAD is increasing along with the rising prevalence of conventional risk factors for CAD in Bangladesh 31 . Present health transition from predominance of infections to the preponderance of cardiovascular disorders, such as hypertension, diabetes and CAD is now responsible for 53% of all deaths 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have revealed that the prevalence of CAD is increasing along with the rising prevalence of conventional risk factors for CAD in Bangladesh 31 . Present health transition from predominance of infections to the preponderance of cardiovascular disorders, such as hypertension, diabetes and CAD is now responsible for 53% of all deaths 10,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other countries, cardiovascular disease (CVD) is a progressive reason for increased mortality and services burden in Bangladesh, a developing country with about 160 million of the population as a country experiencing epidemiological transition (13)(14)(15)(16)(17). However, the precise prevalence and risk factors of CVD is yet to be identified (13). A nationwide survey focusing on the epidemiological aspects of coronary artery diseases in this country is yet to be conducted (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise prevalence and risk factors of CVD is yet to be identified (13). A nationwide survey focusing on the epidemiological aspects of coronary artery diseases in this country is yet to be conducted (13). There is scare research to explore the risk factors and implement prevention strategies for premature deaths (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the chances are 37.5% and 18.3 respectively [2] for having 2 risk factors. In Bangladesh, CAD is responsible for 17% mortality rate [3]. Regular diagnostic approach of CAD relies on coronary angiogram test [4], echo-cardiogram ram (ECG) [5,6], nuclear scan test and exercise stress test.…”
Section: Introductionmentioning
confidence: 99%